Heat- and Mass-Transfer analogy in a bubble column - Verma A.K. (My University, 2025)
Heat- and mass-transfer analogy based on heat, mass, and momentum analogy in pipe flow proposed by Lin et al. (Lin, C. S. Moulton, R. W. Putnam, G. L. Mass Transfer between Solid Wall and Fluid Stream. Ind. Eng. Chem. 1953, 45, 636) has been presented for bubble columns. The ratio of constants for correlations based on the Chilton and Colburn analogy in the case of mass transfer to that for heat transfer has been predicted. It depends on the range of gas velocity and values of Pr and Sc.